KOMUNIKASI PERSUASIF PENGURUS KOPERASI CREDIT UNION DALAM MENINGKATKAN JUMLAH ANGGOTA DI DESA KASIKAN KECAMATAN TAPUNG HULU KABUPATEN KAMPAR - Simon Rio; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Cooperative credit union is a financial institution engaged in the savings and loan owned by its members, and aims for the welfare of its own members. In this case, administrators are those who communicate directly with the members and prospective members. Persuasive communication is done by the cooperative management of the credit unions is the initial approach to potential members with a personal persuasive communication, as well as the confidence of the members to cooperative credit union. This study aims to determine how persuasive communication strategy cooperative management of credit union in increasing the number of members and the cooperative management model of persuasive communication in increasing the number of credit union members.This research used qualitative methods with descriptive approach. This research was done in cooperative credit union on Raya Kasikan Village Sub-District Tapung Hulu Kampar District. There are 17 participants were taken through a purposive sampling technique and snowball sampling technique. Types and sources of data obtained through the primary data and secondary data. Data collection is done with observation to participants, interviews and documentation. This research uses interactive data analysis miles and huberman with an examination of the validity of the data is done through the extension of participation and triangulation.The results of this study indicate that the communication strategies used persuasive cooperative management of credit union in increasing the number of members is by using psychodynamic strategy is administrators taking cognitive approach through education provided to members and prospective members of cooperative credit union, sociocultural strategy is the influence of the environment that makes prospective members would become members in the cooperative credit union, the meaning construction strategy is administrators give a parable to motivate members, and comparasion strategy is administrators gives a comparasion between the cooperative credit union with others financial institutions. The used cooperative management model of persuasive communication of credit union is source, receiver, message, and channel. Keyword: persuasive communication, credit union cooperative